Analisis Kesalahan Siswa pada Tes Kemampuan Dasar Matematika Kelas III Sekolah Dasar - Wahyudi Wahyudi (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2019)
AbstractThe research aims to describe: (1) the types of students’ errors, (2) the causes of students' mistakes, (3) how to fix the students’ mistakes. It is qualitative research. The research subjects are all students and teachers of third grade in the group of Banyumudal Elementary School, Kebumen Subdistrict, in academic year 2018/2019. The results shows that (1) the types of students’ errors are: (a) writing, reading names and numbers symbol (b) sorting numbers, (c) place values, (d) subtracting numbers, (e) multiplying 2 numbers, (f) dividing numbers, (g) mixed count operations, (h) comparing, adding, subtracting fractions with equal denominators, (i) calculating money values, (j) square, rectangular, angular, (k) measuring length, area, weight and time; while (2) the cause of students' mistakes is the lack of understanding in concepts and materials; and (3) how to fix the students’ mistakes is through learning improvement with a focus in the types and causes of student errors.Keywords: error analysis, basic ability test, mathematicsAbstrakTujuan penelitian ini adalah: (1) mendeskripsikan jenis kesalahan siswa, (2) mendeskripsikan sebab kesalahan siswa, (3) mendeskripsikan cara memperbaiki kesalahan siswa. Penelitian ini yaitu Penelitian Kualitatif dengan subjek adalah siswa dan guru kelas III Sekolah Dasar Gugus Banyumudal Kecamatan Kebumen Tahun ajaran 2018/2019. Hasil yang penelitian ini adalah: (1) jenis kesalahan siswa adalah: (a) menulis, membaca nama dan lambang bilangan (b) mengurutkan bilangan, (c) nilai tempat, (d) mengurang bilangan, (e) mengalikan 2 bilangan, (f) membagi bilangan, (g) operasi hitung campuran, (h) membandingkan, menjumlahkan, mengurangkan pecahan dengan penyebut sama., (i) perhitungan nilai uang, (j) persegi, persegi panjang, sudut, (k) pengukuran panjang, luas, berat, dan waktu; (2) penyebab kesalahan siswa adalah kurang memahami konsep dan materi; (3) cara memperbaiki kesalahan siswa adalah melalui pembelajaran perbaikan dengan fokus pada jenis dan penyebab kesalahan siswa. Kata kunci: analisis kesalahan, tes kemampuan dasar, matematika